Penerapan LKPD Berbasis Masalah pada Materi Pembakaran Hidrokarbon melalui Pembelajaran E-Learning untuk Meningkatkan Hasil Belajar dan Sikap Peduli Lingkungan Peserta Didik - Zulyati Zulyati; Sulastri Sulastri; Cut Nurmalia; Yusrizal Yusrizal; Hasan Hasan (Jurnal Penelitian Pendidikan IPA, 2022)
The purpose of this research is for investigating student’s learning outcomes and environmental care attitude of hydrocarbon combustion by applying problem-based worksheet through e-learning. This research used quantitative method with one group pretest-postest design. The sample of this research is the XI MIPA students totalling 29 students. The instrument used of this research was multiple choices test and questionnaire non-test. The data of this research were analysed by using t-test. Based on the analysis result is obtained, there is an enhancement in the average score of students’ abilities from 43.10 become 71.50 and there is a significant difference of student learning outcome after applying problem-based worksheet based on the t-test result, where t-count 25.65 > t-table 1.65. Futhermore, there is also an enhancement on environmental care attitude from 62.54 to 79.95 with N-gain is 47.63 in the medium category. The average score of environmental care attitude for indicators, 1) the attitude towards energy has enhanced from 57.99% to 70.35% with N-gain average is 30.44% in the medium category., 2) the attitude towards humans and environment from 57.29 become 80.84% with N-gain average is 53.24% in the medium category., 3) the attitude towards water from 58.31% to 66.67% with N-gain average is 20.09 in the medium category., 4) Wast management from 54.82% to 60.99% with N-gain average 11.50% in the low medium. Consequently, based on the result is obtained, there is an enhancement of student learning outcome and environmental care attitude by applying problem-based worksheet on the hydrocarbon combustions material through e-learning